Kebijakan Publik Prioritas untuk Menanggulangi Dampak Banjir di Kabupaten Kampar Menggunakan Metode AHP - Fitri Fitri; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin (Politeknik Kampar, 2024)
Flood is a disaster that often occurs in Kampar Regency, Riau, which is caused by a combination of geographical factors, topography, and human activities. This study aims to identify relevant public policies to mitigate the impact of flooding in Kampar Regency using the Analytical Hierarchy Process (AHP) method to determine the priority of public policies that will be recommended to related parties. The results of the study indicate that improving law enforcement, watershed governance, and rehabilitation and conservation of natural resources are the main policies that must be implemented. These findings are expected to be a guideline for local governments in formulating effective mitigation strategies to reduce the impact of flooding in the area.